Lysosomal enzyme activities in polymorphonuclear leukocytes, macrophages, serum, and spleen of conventional, germ-free, and antigen-free Minnesota miniature swine - Ferencík, M; Bergendi, L; Mandel, L; Kovárů, F; Stefanovic, J (Folia microbiologica, 1985)
The activities of lysozyme, myeloperoxidase, and elastase were lower in PMNs and AMs from GF and AF Minnesota miniature piglets than in the leukocytes from their CONV counterparts. In the spleen and serum of gnotobiotic piglets only the levels of lysozyme were slightly reduced. Substantially depressed activities of these LEs were found also in PMNs from precolostral piglets in comparison with PMNs from their CONV mother. The bisassociation of GF piglets with Enterococcus liquefaciens and Escherichia coli caused an increase of LE activities in their AMs, spleens, and sera. Fewer LEs were released after phygocytic stimulation with zymosan from PMNs of GF, AF, and precolostral piglets than from PMNs of CONV animals of the same age. These data suggest that the antigenic-microbial stimulation is important for the development of normal lysosomal enzyme activities in PMNs and AMs from gnotobiotic animals.
Keywords: neutrofily; Animals; gnotobiologické modely; Swine, Miniature; Antigens; Germ-Free Life; antigeny; zvířata; miniaturní prasata; Lysosomes; Macrophages; prasata; Swine; slezina; Neutrophils; lyzozomy; makrofágy; Spleen